A World of Fiction Digital Collections and the Future of Literary History - Bode, Katherine; Project Muse; Project Muse. (Project Muse, 2018)
During the 19th century, throughout the Anglophone world, most fiction was first published in periodicals. In Australia, newspapers were not only the main source of periodical fiction, but the main source of fiction in general. Because of their importance as fiction publishers, and because they provided Australian readers with access to stories from around the world--from Britain, America and Australia, as well as Austria, Canada, France, Germany, New Zealand, Russia, South Africa, and beyond--Australian newspapers represent an important record of the transnational circulation and reception of fiction in this period. Investigating almost 10,000 works of fiction in the world's largest collection of mass-digitized historical newspapers (the National Library of Australia's Trove database), A World of Fiction reconceptualizes how fiction traveled globally, and was received and understood locally, in the 19th century. Katherine Bode's innovative approach to the new digital collections that are transforming research in the humanities are a model of how digital tools can transform how we understand digital collections and interpret literatures in the past.
Abstraction, singularity, textuality: the equivalence of "close" and "distant" reading -- Back to the future : a new scholarly object for (data-rich) literary history -- From world to trove to data : tracing a history of transmission -- Into the unknown : literary anonymity and the inscription of reception -- Fictional systems : network analysis and syndication networks -- "Man people woman life" / "Creek sheep cattle horses" : influence, distinction, and literary traditions.
Issued as part of book collections on Project MUSE.
Includes bibliographical references (pages 229-243) and index.
Description based on print version record.
Keywords: Information storage and retrieval systems -- Newspapers; Transmission of texts; Australian newspapers -- History -- 19th century; Journalism and literature -- Australia -- History -- 19th century; Electronic books; Electronic books